Analisis Yuridis Harta Gono Gini Perspektif Undang-Undang Perkawinan Dan Hukum Islam - Syarif, Azhar (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2024)
The purpose of this research is to understand the legal concepts underlying the regulation of joint marital property (harta gono gini) and to examine the perspective of Islamic law on the division of this property. The type of research conducted is normative legal research. According to Peter Mahmud Marzuki, normative research is the process of finding legal rules, legal principles, or legal doctrines to address the legal issues faced. The results of this study indicate that the division of joint marital property based on customary law concepts is influenced by the kinship system adopted, which may be matrilineal, patrilineal, or parental customary systems. According to religious legal concepts, for Muslims, the provisions regarding joint marital property are regulated in the Compilation of Islamic Law (KHI), while for non-Muslim communities, the provisions of the Civil Code (KUH Perdata) apply. Islamic Sharia law views a clear distinction between the property of husband and wife. The KHI, which is the legal outcome of scholars, considers that the merging of property occurs within marriage using the concept of partnership (syirkah), and acknowledges the existence of joint marital property through the approach of ‘urf (customs and traditions). The distribution of joint marital property in the KHI is regulated to be divided equally, which, although lacking a firm basis, fulfills the concept of justice and is an application of the theory of maqashid sharia to protect five basic interests, including the welfare of individuals, property, and descendants of each couple. Tujuan penelitian ini adalah untuk mengetahui konsep hukum yang mendasari pengaturan harta gono gini dan untuk mengetahui tinjauan hukum Islam terhadap pembagian harta gono gini. Jenis penelitian yang digunakan adalah penelitian hukum normatif. Menurut Peter Mahmud Marzuki penelitian normative adalah proses untuk menemukan suatu aturan hukum, prinsip-prinsip hukum, maupun doktrin-doktrin hukum guna menjawab isu hukum yang dihadapi. Hasil penelitian ini menunjukan bahwa pembagian harta gono gini berdasarkan konsep hukum adat dipengaruhi oleh sistem kekerabatan yang dianut yaitu sistem sistem matrilineal, sistem patrilineal atau sistem adat parental. Berdasarkan konsep hukum agama maka bagi orang Islam, berlaku ketentuan harta gono gini yang diatur dalam KHI, sementara itu bagi masyarakat non muslim berlaku ketentuan KUH Perdata. Hukum  syariah Islam lebih memandang adanya keterpisahan antara harta suami dan istri. KHI yang merupakan hasil hukum para ulama memandang bahwa pencampuran harta terjadi dalam perkawinan dengan menggunakan konsep syirkah, dan mengakui keberadaan harta gono gini melalui pendekatan ‘urf (adat dan kebiasaan). Pembagian harta gono gini di dalam KHI diatur dengan dibagi sama rata/seperdua, aturan tersebut walaupun tidak mempunyai dasar tetapi memenuhi konsep keadilan dan merupakan aplikasi dari teori maqashid syariah untuk menjaga lima kemaslahatan pokok diantaranya adalah menjaga kemaslahatan diri, harta dan keturunan masing-masing pasangan